High quality draft genomic sequence of Flavobacterium enshiense DK69T and comparison among Flavobacterium genomes. Issue 1 (December 2015) - Zeng, Zhipeng; Chen, Chong; Du, Hailun; Wang, Gejiao; Li, Mingshun
Abstract Flavobacterium enshiense DK69T is a Gram-negative, aerobic, rod-shaped, non-motile and non-flagellated bacterium that belongs to the familyFlavobacteriaceae in the phylumBacteroidetes. The high quality draft genome of strain DK69T was obtained and has a 3, 375, 260 bp genome size with a G + C content of 37.7 mol % and 2848 protein coding genes. In addition, we sequenced five more genomes ofFlavobacterium type strains and performed a comparative genomic analysis among 12Flavobacterium genomes. The results show some specific genes within the fish pathogenicFlavobacterium strains which provide information for further analysis the pathogenicity.